Non-alcoholic fatty liver disease: Epidemiology and non-invasive assessment / Chan Wah Kheong - Chan, Wah Kheong (2014)

(untitled)
This thesis consists ten chapters and presents the findings from four research projects in eight areas of interest concerning the epidemiology and non-invasive assessment of nonalcoholic fatty liver disease (NAFLD). In a cross-sectional study of 399 patients with diabetes mellitus in the Diabetic Clinic, University of Malaya Medical Centre, the prevalence of NAFLD was 49.6% and was highest among the Malays and the Indians compared to the Chinese. Further analysis revealed that low level of physical activity and high percentage calorie intake from fat, high cholesterol food and high saturated fatty acid food was associated with NAFLD in centrally obese but not in lean patients with diabetes mellitus. In addition, NAFLD was not found to be associated with ischemic heart disease in patients with diabetes mellitus. In a separate study on 35 NAFLD patients with paired liver biopsy over a mean interval of 6.4 years, it was found that patients can undergo significant disease progression, and fibrosis is irreversible without specific interventions. From the studies on non-invasive assessment of NAFLD, controlled attenuation parameter was found to be excellent for the detection of significant hepatic steatosis but less useful for distinguishing the different grades of significant hepatic steatosis, while plasma M30 was found to be less useful for the diagnosis of non-alcoholic steatohepatitis among NAFLD patients. The use of liver stiffness measurement for patients with indeterminate and high NAFLD fibrosis scores allowed accurate prediction of advanced fibrosis and reduced the number of patients requiring a liver biopsy. In the study on 472 students at the Faculty of Medicine, University of Malaya, the prevalence of NAFLD was 8.1% and was again highest among the Indians and the Malays compared to the Chinese. This study confirmed that differences in the prevalence of NAFLD among the different ethnic groups in Malaysia can be observed as early as young adulthood.